LEVELLING MESIN BUBUT LZ 330 G MENGGUNAKAN ALAT UKUR SPIRIT LEVEL - Roberth Marshall Ratlalan; Nurisma Maharani (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2023)
The leveling process is the initial stage before operating a lathe. The test will be carried out if the flatness on the machine and the results have deviated greatly, it must be leveled on the lathe. This study aims at a high level of accuracy of machine tools in the form of leveling on three types of Gedee Weiler LZ 330 G lathes located at the AK-Manufaktur Bantaeng Manufacturing Workshop. This type of research is categorized as quantitative research which is an inductive, objective and scientific method in which the data is processed in the form of numbers or statements which are then analyzed. Data from the test results of the M1 lathe with the longitudinal tilt direction towards the off head, while in the transverse position the slope direction is towards the rear slide. Flatness deviation reaches 1.06 mm in the longitudinal position and 0.15 mm in the transverse position. For the M2 lathe, the direction of the longitudinal slope is the direction of the off head, while in the transverse position, the direction of the slope of the fore runway. Deviation of flatness reaches 1.3 mm in the longitudinal position and 1.75 in the transverse position and the M3 lathe with the longitudinal slope direction towards the off head, while in the transverse position the slope direction is towards the front of the runway. Flatness deviation reaches 1.65 mm in the longitudinal position and 10.15 mm in the transverse position.